Lelgal analysis of velhiclel seizure by debt collectors based on constitutional court decision 18/PUU-XVII/2019 - Shalwa Shalsabila; Sulkiah Hendrawati; Wahyudi Wahyudi (Journal of Law Science, 2024)
This study analyzes the legality of motor vehicle repossession by debt collectors under fiduciary agreements following Constitutional Court Decision No. 18/PUU-XVII/2019. Unilateral repossession practices by financing companies through third parties often result in violations of debtor rights, legal disputes, and social unrest. The research employs a normative juridical method with a statutory approach, court decision analysis, and legal literature review to evaluate its conformity with the principle of legal protection. The purpose of this study is to explain the legal implications of Constitutional Court Decision No. 18/PUU-XVII/2019 on the enforcement mechanism of fiduciary guarantees and to assess the extent to which debtor protection can be realized without neglecting creditors’ rights. The findings show that repossession without debtor consent or court authorization contradicts Article 15 of the Fiduciary Guarantee Law and the principle of due process. Recommendations include regulatory strengthening, debt collector certification, and the implementation of responsive laws to prevent arbitrary repossession practices.